Herbal prescription Chang'an II repairs intestinal mucosal barrier in rats with post-inflammation irritable bowel syndrome - Wang Feng-yun; Su Min; Zheng Yong-qiu; Wang Xiao-ge; Kang Nan; Chen Ting; Zhu En-lin; Bian Zhao-xiang; Tang Xu-dong (Acta Pharmacologica Sinica; Vol 36, No 6 (June 2015): Acta Pharmacologica Sinica (Special Feature: Fangjiomics in Traditional Chinese Medicine: Progress and Perspective), 2017)
Aim: The herbal prescription Chang'an II is derived from a classical TCM formula Tong-Xie-Yao-Fang for the treatment of liver-qi stagnation and spleen deficiency syndrome of irritable bowel syndrome (IBS). In this study we investigated the effects of Chang'an II on the intestinal mucosal immune barrier in a rat post-inflammation IBS (PI-IBS) model. Methods: A rat model of PI-IBS was established using a multi-stimulation paradigm including early postnatal sibling deprivation, bondage and intrarectal administration of TNBS. Four weeks after TNBS administration, the rats were treated with Chang'an II (2.85, 5.71 and 11.42 g·kg−1·d−1, ig) for 14 d. Intestinal sensitivity was assessed based on the abdominal withdrawal reflex (AWR) scores and fecal water content. Open field test and two-bottle sucrose intake test were used to evaluate the behavioral changes. CD4+ and CD8+ cells were counted and IL-1β and IL-4 levels were measured in intestinal mucosa. Transmission electron microscopy was used to evaluate ultrastructural changes of the intestinal mucosal barrier. Results: PI-IBS model rats showed significantly increased AWR reactivity and fecal water content, and decreased locomotor activity and sucrose intake. Chang'an II treatment not only reduced AWR reactivity and fecal water content, but also suppressed the anxiety and depressive behaviors. Ultrastructural study revealed that the gut mucosal barrier function was severely damaged in PI-IBS model rats, whereas Chang'an II treatment relieved intestinal mucosal inflammation and repaired the gut mucosal barrier. Furthermore, PI-IBS model rats showed a significantly reduced CD4+/CD8+cell ratio in lamina propria and submucosa, and increased IL-1β and reduced IL-4 expression in intestinal mucosa, whereas Chang'an II treatment reversed PI-IBS-induced changes in CD4+/CD8+ cell ratio and expression of IL-1β and IL-4. Conclusion: Chang'an II treatment protects the intestinal mucosa against PI-IBS through anti-inflammatory, immunomodulatory and anti-anxiety effects.